MSMEs in Digital Transformation: Determinants of QRIS E-Payment Acceptance - Fauziah, Farah; Made Sudarma; Erwin Saraswati (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
This study is using a combination of TAM and TPB to explore the intention to use QRIS electronic payments among SMEs in Malang. The sample was collected through a survey and a representative sample of 155 SMEs was obtained. This study used SEM-PLS to analyze the construct model. The results stated that perceived usefulness, subjective norms and digital literacy significantly affect the intention to be using QRIS electronic payments. The results also show that intention to use QRIS and digital literacy significantly affect digital transformation. Interestingly, perceived convenience has the opposite effect in this study. Other factors influencing the adoption of electronic payments by SMEs and their impact on digital transformation should be explored in the future. This study should help to understand and enrich the theoretical framework so that it can be applied to increase the use of digital payments QRIS and increase digital transformation in the SME sector.